PRESERVING CULTURAL HERITAGE: A CASE STUDY OF CULTURAL TOURISM SUSTAINABILITY DEVELOPMENT IN GIRSANG SIPANGAN BOLON, INDONESIA - Nurlisa GINTING; Wahyuni ZAHRAH; Amran HAMZAH; Badaruddin MOHAMED; Antonella TROMBADORE; Utari DAMANIK (Geo Journal of Tourism and Geosites)
The objective of this study is to assess the sustainability of cultural aspects within sustainable tourism and to investigate the current conditions and procedures involved in preserving cultural heritage in three selected tourist destinations in Girsang Sipangan Bolon District, North Sumatra Province, Indonesia. This research employs a mixed-methods approach, consisting of quantitative data gathered from questionnaires distributed to 120 respondents (local tourists and residents) and qualitative data obtained through interviews with relevant government officials and direct observations at the study sites. The study's findings reveal the successful preservation of Girsang Sipangan Bolon's culture, which continues to impress many people. However, it is crucial that all stakeholders continue to safeguard local culture to ensure its ongoing preservation. It is hoped that this research can serve as a reference and a consideration in developing cultural tourism, as well as raising awareness of the region's extraordinary cultural diversity. This should be enhanced in terms of management and promotion, extending from the local community to the international level, positioning this area as a key cultural tourism destination within the Lake Toba region, North Sumatra, Indonesia.